2023
DOI: 10.3389/fmicb.2023.1299950
|View full text |Cite
|
Sign up to set email alerts
|

Four new Microbacterium species isolated from seaweeds and reclassification of five Microbacterium species with a proposal of Paramicrobacterium gen. nov. under a genome-based framework of the genus Microbacterium

Soon Dong Lee,
Hong Lim Yang,
In Seop Kim

Abstract: The taxonomic relationships of 10 strains isolated from seaweeds collected from two beaches in Republic of Korea were studied by sequencing and analyses of 16S rRNA genes and whole genomes. For the construction of a more reliable and robust 16S rRNA gene phylogeny, the authentic and nearly complete 16S rRNA gene sequences of all the Microbacterium type strains were selected through pairwise comparison of the sequences contained in several public databases including the List of Prokaryotic names with Standing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…The core genome-based phylogenetic tree ( and Table S2) showed that the three isolates belonged to cluster IV ( M. testaceum clade) defined in the previous work [13]. Strains KSW2-29 T and KSW4-17 T formed a tight cluster with M. hydrothermale CGMCC 1.12512 T , while strain KSW2-21 T was most closely associated with M. testaceum NBRC 12675 T .…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…The core genome-based phylogenetic tree ( and Table S2) showed that the three isolates belonged to cluster IV ( M. testaceum clade) defined in the previous work [13]. Strains KSW2-29 T and KSW4-17 T formed a tight cluster with M. hydrothermale CGMCC 1.12512 T , while strain KSW2-21 T was most closely associated with M. testaceum NBRC 12675 T .…”
Section: Resultsmentioning
confidence: 69%
“…Bootstrap support values (>50 %) are shown at the branches. Members of the genomic clusters V and VIII defined by Lee et al [13] are listed in Table S2. Bar, 0.01 substitutions per nucleotide position.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations